Value-semantic targeting of individuals with different levels of burnout - Матвієнко, Лариса Іванівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
This article deals with the issues of emotional burnout and its relationship with value-semantic sphere of personality. The study presents the results of theoretical analysis of the problem described in modern psychological literature, with emphasis on the existential axiological aspect of the analysis of burnout as relevant. The empirical research studied phase indicators and dominant symptoms of emotional burnout among specialists of socionomy occupations. The correlation analysis revealed significant inverse relationship between the indicators of meaningfulness of life and level of emotional burnout.